Cognitive profiles in pediatric unilobar vs. multilobar epilepsy. (November 2022) - Moorhouse, Frederik Jan; Cornell, Sonia; Gerstl, Lucia; Wagner, Johanna; Tacke, Moritz; Roser, Timo; Heinen, Florian; von Stülpnagel, Celina; Vollmar, Christian; Kunz, Mathias; Ramantani, Georgia; Borggraefe, Ingo
Abstract: Objectives: We aimed to determine how cognitive impairment relates to the extent of the presumed epileptogenic zone in pediatric focal epilepsies. We analyzed the cognitive functions in unilobar compared to multilobar focal epilepsy patients that underwent neuropsychological testing at a tertiary epilepsy center. Methods: We assessed cognitive functions of pediatric focal epilepsy patients with the German version of the Wechsler Intelligence Scales that measures full-scale IQ and subcategories. We assessed differences in IQ and epilepsy-related variables between unilobar and multilobar epilepsy patients. Results: We included 62 patients (37 unilobar, 25 multilobar), aged 10.6 ± 3.7 years. Full-scale IQ values were significantly higher in unilobar (93.6 ± 17.7, 95% CI 87.7–99.6) than in multilobar epilepsy patients (77.3 ± 17.2, 95% CI 69.3–85.0; p  = 0.001). In all but one IQ subcategory (working memory), significantly higher values were measured in unilobar than in multilobar epilepsy patients. The proportion of unilobar epilepsy patients with severe cognitive impairment (8.3%) and below-average intelligence (30.5%) was lower compared to multilobar epilepsy patients (47.6% and 61.9%; p  = 0.002 and p  = 0.021, respectively). Epilepsy onset occurred earlier in multilobar (4.0 years, 95% CI 2.6–5.5, SD ± 3.4 years) than in unilobar epilepsy patients (7.0 years, 95% CI 5.5–8.5, SD ± 4.4 years, p  = 0.008). Conclusions: Pediatric multilobar epilepsy patients face more cognitive issues than unilobar epilepsy patients on average. Our findings should help to identify children and adolescents who are most at risk for impaired cognitive development. A limitation of our study is the simple division into unilobar and multilobar epilepsies, with no specific account being taken of etiology/epilepsy syndrome, which can have a profound effect on cognition. Highlights: Multilobar epilepsies manifest earlier than unilobar epilepsies. Multilobar epilepsies present a lower mean IQ than unilobar epilepsies. Multilobar epilepsies entail higher rates of cognitive impairment than unilobar epilepsies.